Parcerias público-privadas na presença de seleção adversa: uma análise numérica - Rodrigues, Rafael Mourão dos Santos (2010)
This dissertation analyzes the optimality of public-private partnerships (PPP) in an adverse selection framework. More speciÖcally, I analyze whether the tasks of building and operating an infrastructure for public services should be performed by a consortium or if it should be performed by individually contracted Örms. For that, in a departure from the existent literature, focused on problems of incomplete contracting and moral hazard, I build a multidimensional adverse selection model where the Örms are privately informed and can exert a non-observable e§ort in each task, with the existence of an externality between them, in an extension of the La§ont and Tirole (1986) model. After isolating some conditions under which PPP dominates usual procurement contracts, I rely on numerical analysis to better comprehend the modelís solution, which turns out to be heavily dependant on the correlation between the Örms private information parameters.